Genetic variations of three important antioxidative enzymes SOD2, CAT, and GPX1 in nonalcoholic steatohepatitis. Issue 1 (1st October 2020) - Huang, Yi-Shin; Chang, Tien-En; Perng, Chin-Lin; Huang, Yi-Hsiang
Abstract : Background: Nonalcoholic steatohepatitis (NASH) is closely related to reactive oxygen species (ROS). Superoxide anion radicals, the main product of ROS, can be reduced by manganese superoxide dismutase (SOD2) to hydrogen peroxide, which is further reduced by catalase (CAT) and glutathione peroxidase (GPX) to water. We aimed to investigate the association between the most important genetic variants of SOD2, CAT, and GPX1 and susceptibility to NASH. Methods: A total of 126 adults with liver tissue-verified NASH, 56 patients with liver tissue-verified nonalcoholic fatty liver (NAFL), and 153 healthy controls were enrolled. Their DNA profiles were retrieved for genotype assessment of SOD2 47T>C (rs4880), CAT -262C>T (rs1001179), and GPX1 593C>T (rs1050450) variation. Results: There were statistical differences between the SOD2 and CAT genotypes across the NASH, NAFL, and control groups, but not GPX1 . The NASH group had a significantly higher frequency of subjects with SOD2 C allele (38.8%) compared with the NASL group (25.0%) and the controls (22.9%, p = 0.010). Similarly, the NASH group had a significantly higher percentage of subjects with CAT T allele (23.0%) compared with the NAFL group (10.7%) and the controls (7.2%, p = 0.001). For subjects with both the SOD2 C allele and CAT T allele, 88.2% were in the NASH group. After adjusting for confounders, the CAT mutant T allele and SOD2 mutant C allele were still the highest independent risk factors for NASH (odds ratio [OR] 3.10 and 2.36, respectively). In addition, there was a synergistic effect for those two alleles and the occurrence of NASH with an adjusted OR of 8.57 ( p = 0.030). Conclusion: The genetic variations of CAT and SOD2 may increase the risk of NASH, which may aid in the screening of patients who are at high risk of NASH, and offer a potential anti-oxidant targeting route for the treatment of NASH.